Uso de stent en la angioplastia del paciente con infarto agudo de miocardio - Rodríguez Blanco, Suilbert; Almeida Gómez, Javier (CorSalud, 2014)
Uso de stent en la angioplastia del paciente con infarto agudo de miocardio